Understanding the synergistic effects, optical and electronic properties of ternary Fe/C/S‐doped TiO2 anatase within the DFT + U approach. Issue 5 (23rd September 2017) - Opoku, Francis; Govender, Krishna Kuben; van Sittert, Cornelia Gertina Catharina Elizabeth; Govender, Penny Poomani
Abstract: Although TiO2 is an efficient photocatalyst, its large band gap limits its photocatalytic activity only to the ultraviolet region. An experimentally synthesized ternary Fe/C/S‐doped TiO2 anatase showed improved visible light photocatalytic activity. However, a theoretical study of the underlying mechanism of the enhanced photocatalytic activity and the interaction of ternary Fe/C/S‐doped TiO2 has not yet been investigated. In this study, the defect formation energy, electronic structure and optical property of TiO2 doped with Fe, C, and S are investigated in detail using the density functional theory + U method. The calculated band gap (3.21 eV) of TiO2 anatase agree well with the experimental band gap (3.20 eV). The defect formation energy shows that the co‐ and ternary‐doped systems are thermodynamically favorable under oxygen‐rich condition. Compared to the undoped TiO2, the absorption edge of the mono‐, co‐, and ternary‐doped TiO2 is significantly enhanced in the visible light region. We have shown that ternary doping with C, S, and Fe induces a clean band structure without any impurity states. Moreover, the ternary Fe/C/S‐doped TiO2 exhibit an enhanced photocatalytic activity, a smaller band gap and negative formation energy compared to the mono‐ and co‐doped systems. Moreover, the band edges of Fe/C/S‐doped TiO2 align well with the redox potentials of water, which shows that the ternary Fe/C/S‐doped TiO2 is promising photocatalysts to split water into hydrogen and oxygen. These findings rationalize the available experimental results and can assist the design of TiO2 ‐based photocatalyst materials. Abstract : TiO2 anatase is the most extensively explored semiconductor photocatalyst owing to its superior photoactivity, cost‐effectiveness, nontoxicity, resistance to photo‐corrosion, high quantum efficiency, and chemical stability. The formation energy, electronic structure, and optical property of ternary Fe/C/S‐doped TiO2 anatase are investigated using the DFT +  U approach. The ternary Fe/C/S‐doped TiO2 exhibit an enhance photocatalytic activity, a smaller band gap and smaller formation energy compared to the un‐doped TiO2 .